Combining analyses of metabolite profiles and phosphorus fractions to explore high phosphorus utilization efficiency in maize. (18th March 2022) - Han, Yang; Hong, Wanting; Xiong, Chuanyong; Lambers, Hans; Sun, Yan; Xu, Zikai; Schulze, Waltraud X; Cheng, Lingyun
Abstract : Analyses of phosphorus (P) fractions and non-targeted metabolomics suggest that efficient utilization of lipid P and nucleic acid P pools and enhanced expression of the shikimate pathway contribute to efficient P utilization in maize leaves. Abstract: Phosphorus (P) limitation is a significant factor restricting crop production in agricultural systems, and enhancing the internal P utilization efficiency (PUE) of crops plays an important role in ensuring sustainable P use in agriculture. To better understand how P is remobilized to affect crop growth, we first screened P-efficient (B73 and GEMS50) and P-inefficient (Liao5114) maize genotypes at the same shoot P content, and then analyzed P pools and performed non-targeted metabolomic analyses to explore changes in cellular P fractions and metabolites in maize genotypes with contrasting PUE. We show that lipid P and nucleic acid P concentrations were significantly lower in lower leaves of P-efficient genotypes, and these P pools were remobilized to a major extent in P-efficient genotypes. Broad metabolic alterations were evident in leaves of P-efficient maize genotypes, particularly affecting products of phospholipid turnover and phosphorylated compounds, and the shikimate biosynthesis pathway. Taken together, our results suggest that P-efficient genotypes have a high capacity to remobilize lipid P and nucleic acid P and promote the shikimate pathway towards efficient P utilization in maize.